Rasisme dan Kaum Tertindas: Perjuangan Nir-Kekerasan Martin Luther King Jr., dan Implikasinya Bagi Masyarakat Papua - Marthinus Ngabalin (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
Nonviolence struggle on the issue of racism: The White and Black in the United States voiced by Martin Luther King, Jr. The impact was that he won the Nobel Peace Prize for speaking out the peaceful side in every action for blacks. Learning from King, regarding the issue of racism in Papua, the path of peace by presenting love must be the most important thing to promote peace and humanity. The method used in the research is qualitative research with a literature study approach. This study aims to explain the problem of racism, describe Martin Luther King's, background and explain the main points of Martin Luther King's struggle, racism, and humanity where everyone is required to fight violence nonviolently.